Virtuous Vice : Homoeroticism and the Public Sphere - Clarke, Eric O., 1963- (Book collections on Project MUSE., 2000)
In this daring study of queer life and the public sphere, Eric O. Clarke examines the effects of inclusion within public culture. Departing from studies that emphasize homophobia and its mechanisms of exclusion, Virtuous Vicedetails how mainstream efforts to represent queers affirmatively continually fall short of full democratic enfranchisement. Clarke draws on contemporary writings along with late-eighteenth- and nineteenth-century English and European cultural history to investigate how concepts of value, representation, and homoeroticism have interacted and circulated in the West since the Enlightenment. Examining the role of eroticism in citizenship and why only normalizingconstructions of homosexuality enable inclusion, Clarke reconsiders the work of Habermas and Foucault in relation to contemporary visibility politics, Kants moral and political theory, Marxs analysis of value, and the sexualized dynamics of the Victorian cultural public sphere. The juxtaposition of Habermas with Foucault reveals the surprising value of reading the former in the context of queer politics and the usefulness of the theory of the public sphere for understanding contemporary identity politics and the visibility politics of the 1990s. Examining how a host of nonsexual factors impinge historically upon the constitution of sexual identities and practices, Clarke negotiates the relation between questions of publicity and categories of value. Discussions of television sitcoms (such asEllen), marketing techniques, authenticity, and literary culture add to this daring analysis of visibility politics. As a critique of the claim that equal representation of gays and lesbians necessarily constitutes progress, this significant intervention into social theory will find enthusiastic readers in the fields of Victorian, cultural, literary, and gay and lesbian studies, as well as other fields engaged with categories of identity.